Effect of Xylazine, Midazolam and Dexmedetomidine Preanaesthetics on Changes in Intraocular Pressure in Rats - Yener, Kerem; Yavuz, Ünal; Hayat, Ali; Dikmen İlginoğlu, Kübra; Karadağ, Mehmet Salih; Hurma, Mehmet Sıdık (Acta Scientiae Veterinariae, 2024)
Background: Intraocular pressure (IOP) is influenced by a variety of factors, including intraocular fluid volume, choroidal blood volume, and vitreous volume. Abnormal IOP can result in visual issues, with ocular hypotension potentially leading to retinal detachment and ocular hypertension, causing damage to the retina and optic nerve, which can lead to glaucoma. Anaesthetic agents and body position, such as the Trendelenburg position, can significantly affect IOP. While there is extensive research on IOP changes at various positions in humans, data on the effects of the prone and Trendelenburg positions in both human and veterinary medicine are limited. The Trendelenburg position, which involves tilting the head 15°-45° up or down, is commonly used in laparoscopic and bariatric surgeries and in veterinary procedures, such as ovariohysterectomy and castration. However, the impact of this position on IOP, particularly when combined with anaesthetics, has not been well documented. Preanaesthetic agents, such as xylazine (XYL) and dexmedetomidine (DEX), alpha-adrenoreceptor agonists, and midazolam (MID), a benzodiazepine, can influence intraocular pressure (IOP). This study evaluated the impact of these agents on IOP in Wistar albino rats positioned in reverse Trendelenburg (RTr), a common position in veterinary surgery, to assess their safe use. Materials, Methods & Results: The rats were randomly divided into 3 groups: DXM group [0.75 μg/kg, n=7], MID [5 mg/kg, n=7], and XYL [10 mg/kg, n = 7]. Intraperitoneal injections were administered, and IOP was measured using an Icare Tonovet Plus tonometer at baseline (T0) and at intervals 5 (T5), 10 (T10), 15 (T15), 30 (T30), 45 (T45), 60 (T60), and 90 (T90) min) post-anaesthesia. The rats were immobilized at a 15-degree angle for 90 min. Six consecutive IOP measurements were averaged for each time point. Sedation levels were assessed using a numerical rating scale. In-group measurements and statistical evaluations showed no significant differences at T0 between the DXM, MID, and XYL groups. A decrease in IOP was observed at T15, T30, T45, T60, and T90 in all groups (P < 0.05), with the lowest values at T45 in the XYL group and T60 in the DXM and MID groups. No significant differences were observed between the groups; however, sedation score (SS) increased significantly at T45 and T60, correlating with the lowest IOP values compared to T0 (P < 0.05). The XYL group showed the fastest onset (2.44 ± 1.2 min) and longest duration (80.55 ± 6.56 min) of sedation, although these differences were not statistically significant. The findings of this study suggest that preanaesthetic administration of DXM, MID, and XYL can lead to significant decreases in IOP during deep sedation in the RTr position. Discussion: This is particularly important in veterinary medicine, where research on IOP is limited, particularly in relation to positioning during surgery. Previous studies in horses and cats have shown varying effects of surgical position on IOP, with significant increases in the dorsal and Trendelenburg positions. Human studies have indicated that RTr position can reduce IOP, especially with a greater head angle. This study found that the Tonovet Plus rebound tonometer provides reliable measurements, lending credence to its findings. Further research is required to understand the impact of anaesthetics on IOP across different species and surgical positions. This study suggests that DXM, MID, and XYL have minimal effects on IOP in the RTr position and can be safely utilized in procedures, such as ovariohysterectomy and castration, contributing to the development of strategies for preventing POVL in veterinary medicine and informing human surgical practices. Keywords: intraocular pressure, reverse trendelenburg position, preanaesthesia.